Internet Addiction & Loneliness Among tenth grades students in Al- Sharqiya North at Sultanate of Oman - Alkhawaja, Abdelfattah Mohammed Saeed; Alshabibi, Issa Saleh Ahmed (Journal of Educational and Psychological Sciences, 2020)
The present study was designed to determine the relationship between Internet addiction & loneliness, based on a sample of tenth grades students in Al- Sharqiya North at Sultanate of Oman during coronavirus world health issues (n = 165), 83 male, 82 female. Descriptive method was used. Findings show that there is a negative relationship (α ≤ 0.05) between students’ Internet addiction level & the loneliness level. There are statistically significant differences in the averages of Internet addiction among students by gender variable (male, female) in favor of males, no statistically significant differences in the degree of loneliness by gender variable (male, female), level of internet addiction in the sample are low(1.55), and level of psychological loneliness moderate (2.90). Based on the results, the researchers presented a set of recommendations and proposals to regulate the use of the Internet and prevent the risks of addiction and psychological loneliness.
Keywords: Internet Addiction; Loneliness; tenth grades students at Sultanate of Oman; Sultanate of Oman